IMPACT OF INSULIN RESISTANCE ON REPRODUCTIVE OUTCOMES IN WOMEN WITH PCOS - Hlukhava, Yuliya; Skadorva, Nadzeya; Gurskii, Vladimir; Bohdzel, Maryia; Babkova, Krystsina; Ilina, Iuliia; Korpacka, Alicja; Borowiecka, Patrycja Anna; Proborshch, Pavel; Sazon, Raman (International Journal of Innovative Technologies in Social Science, 2026)
Insulin resistance (IR) is a key metabolic abnormality in polycystic ovary syndrome (PCOS) and is strongly linked to reproductive dysfunction. However, the specific impact of insulin resistance on reproductive outcomes remains unclear. This review explores the current evidence on the impact of insulin resistance on reproductive results in women with PCOS. A systematic search of PubMed/MEDLINE and Google Scholar was performed to identify relevant studies published through March 2025.Research consistently demonstrates a correlation between insulin resistance, anovulation, ovulatory problems, and an increased risk of miscarriage. This could also raise the likelihood of developing gestational diabetes and may adversely impact results in assisted reproductive technology (ART). Although obesity is often seen as a contributing factor, many studies indicate that insulin resistance alone can considerably impact reproductive outcomes. Elevated insulin levels can increase ovarian androgen production, decrease sex hormone-binding globulin (SHBG), and disrupt normal follicular development. Interventions that enhance insulin sensitivity, including lifestyle modifications and, when appropriate, metformin treatment, can improve metabolic health and potentially lead to better reproductive outcomes. Insulin resistance plays a significant role in causing reproductive dysfunction in women with PCOS, highlighting how important it is to evaluate and manage metabolic health as a vital part of fertility treatment.